Flow Structure Transition and Hysteresis of Turbulent Mixed Convection Induced by a Transverse Buoyant Jet. (October 2021) - Wu, J.Y.; Lv, R.R.; Huang, Y.Y.; Yang, G.
Highlights: LES approach is utilized to reproduce the flow field of the mixed convection induced by transverse buoyant jet. Two types of stable flow structures are studied for different R e h and R a H . A hysteresis phenomenon is observed in the flow structure transition. The critical points of transition for different hysteresis curves are highlighted in a R e h - R a H map. Abstract: The large eddy simulation approach is conducted using the dynamic Smagorinsky model and Favre-averaging method to investigate the flow structure transition and hysteresis phenomenon of mixed convection induced by a transverse buoyant jet, based on the opensource computational fluid dynamics package of the OpenFOAM software. The comparison with the available experimental data proves that this model has good adaptability in reproducing the flow structure and temperature distribution of such a flow field. The results are obtained for Reynolds numbers ranging from 120 to 792, and Rayleigh numbers ranging from 1 . 8 × 1 0 9 to 6 . 5 × 1 0 9 . Two types of stable flow structures are observed and systematically studied for different dimensionless parameters, i.e., a clockwise structure dominated by the inertial force, and a counterclockwise structure dominated by the buoyancy force. A hysteresis phenomenon is observed in the flow structure transition, corresponding to the noncoincidence of the first and second transition points. Furtherly, the critical points of transition for different hysteresis curves are highlighted in a Reynolds-number–Rayleigh-number map indicating three flow-regime zones. The transition of flow structure occurs only when the state point moves from the transition zone to another zone across the transition curve.